Alzheimer Disease in Down Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 1989)
A clinical prospective study of dementia of the Alzheimer type in 96 individuals with Down syndrome over age 35 years is reported from the Eunice Kennedy Shriver Center, Waltham, MA and the Massachusetts General Hospital and Harvard Medical School, Boston, MA.